Kinematic Analysis of Long Stroke Pumping Unit with Post Pulley - Sun Wenbin; Zhou Sizhu; Wu Bangxiong; Lü Zhipeng (Jixie chuandong)
In view of the shortcomings of high peak of crank torque and polished rod load,short stroke and serious wear of steel wire rope,the structural characteristics of the conventional beam pumping unit are analyzed. On the basis of that,the post pulley mechanism that change with the displacement of the suspended point and adjust the balance arm is designed. The steel belt is used to replace the traditional steel wire rope to fix on the post pulley. In the process of changing the balance arm post pulley driven steel belt around it to increase the stroke and reduce the friction loss. And the kinematic characteristics of this oil pumping unit are analyzed and calculated. Using the conventional beam pumping unit of CYJ10-1. 8-200 to calculate and analysis and find that the post pulley mechanism that is used has made the peak displacement of suspended point increase about150%. The solid model of the oil pumping unit 1∶ 10 is built and tested. The results show that the calculation and analysis results of this oil pumping unit are in accordance with the experimental results. The correctness of the calculation and analysis results of suspension point kinematic characteristics is verified.